Socialization of Malaria as Endemic in Iran (Communication Analysis) - Roedyati, Joevi (Jurnal sosial dan sains, 2025)
This study examines the endemic nature of malaria in Iran, focusing on the impact of climate change and government initiatives on malaria transmission. Using literature reviews and analyses of current health policies, the research highlights the significant increase in malaria cases due to flooding and the expansion of mosquito habitats. The World Health Organization (WHO) and the Iranian Ministry of Health have initiated collaborative projects to combat malaria through financial support and strategic health interventions. The findings emphasize the importance of continued investment in malaria prevention, community engagement, and the effective use of resources to eradicate this infectious disease in vulnerable regions of Iran.